Molecular analysis of the AGXT gene in Syrian patients suspected with primary hyperoxaluria type 1 - Hossam Murad; Mohamad Baseel Alhalabi; Amir Dabboul; Nour Alfakseh; Mohamad Sayah Nweder; Youssef Zghib; Hala Wannous (BMC, 2021)
Abstract Background Characterization of the molecular basis of primary hyperoxaluria type 1 (PH-1) in Syria has been accomplished through the analysis of 90 unrelated chromosomes from 45 Syrians patients with PH-1 from different regions. Methods Alanine glyoxylate aminotransferase (AGXT) gene mutations have been analyzed by using molecular detection methods based on the direct DNA sequencing for all exons of the AGXT gene. Results Seventeen pathogenic mutations were detected in our patients. Six mutations were novels. The three most frequent mutations were c.33_34insC (p.Lys12fs) in Exon 1, c.584 T < G; p.Met195Arg in exon 5 and c.1007 T > A (p.Val336Asp) in exon 10, with a frequency of 33.3%, 12.2%, and 11.1%, respectively. Conclusion DNA sequencing used in this study can offer a useful method to investigate the mutations in Syrian PH-1 patients, and could offer an accurate tool for prenatal diagnosis and genetic counseling.